Defending an icon: the Matsulu Centre for Rhino Defense - Bosman, Ruan (My University, 2017)
In light of an increasing scientific and social focus on unsustainable human practices, mankind’s dominant relationship with the natural world is now being challenged. Few phenomena demonstrate this destructive relationship better than the growing number of animals being driven to extinction through human actions. The most notable of these, within the South African context, is the devastation of rhinoceros populations caused by illegal poaching, particularly in the Kruger National Park. In dealing with this issue, we have a unique opportunity to embody and catalyse a sustainable paradigm shift. Such a shift would seek to transition mankind into a symbiotic rather than parasitic relationship with the natural world. It would promote the use of cutting edge technologies for the benefit both human and non-human actors, breaking down the separation between man and nature. The resultant hybridised ecosystem would stand as an exemplary manifestation of the long theorised ‘cyborg’ entity, not as individual, but as a new form of habitat and, ultimately, societal organisation. Contextualising such a ‘Cyborgian Nexus’ as a solution to the scourge of rhino poaching is the chief subject of this research report. The Matsulu Centre for Rhino Defense is proposed as a Connected Conservation Centre in the disadvantaged Matsulu community, bordering the Kruger National Park. Its aim is to be the heart of a sophisticated system of cutting edge technologies which allow park rangers to overcome the poaching threat. Through its program as well as its architecture, the project aims to become a recognizable icon of a new relationship between man and nature. One in which human innovation allows for the natural world and the human world to coexist sustainably to the mutual benefit of both.
Thesis is submitted in partial fulfilment for the degree of Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning at the University of the Witwatersrand, Johannesburg, 2017
Keywords: Architecture--Environmental aspects; Wildlife conservation--South Africa; Rhinoceros horn industry--Corrupt practices--South Africa; Matsulu Centre for Rhino Defense (South Africa)